Knowledge Regarding Neonatal Jaundice Management among Mothers: A Descriptive Study Done In a Tertiary Level Hospital of Dhaka City - Huq, Sazia; Hossain, Sarder Mahmud; Haque, Syed Mohammad Tanjilul; Tarafder, Monowar Ahmed (Anwer Khan Modern Medical College Journal, 2017)
Background: Jaundice is the most common clinical condition in the newborn that requires medical attention. This study was carried out in order to assess the knowledge on neonatal jaundice management among the mothers in a selected tertiary level hospital of Dhaka city. Methodology: It was a descriptive type of cross-sectional study. 150 samples were selected by non randomized purposive sampling technique with the administration of a pretested, modified and semistructured questionnaire by face to face interview. Results: Study found that majority of the respondents (76.7%) was in the age group 17-27 years with mean age 23.78±5.397 years. Majority of the respondents (83.3%) had heard about neonatal jaundice previously and 16.7% did not hear about it. Regarding Knowledge on preventive measures of NNJ (neonatal jaundice) 90.6% respondents had knowledge on "Putting jaundiced baby under direct sun light", 62.7% said "Herbal remedies", 48% indicated "Consult with doctor" and 12% had knowledge on "phototherapy". Another major finding from the study was that 7.3% respondents had excellent level of knowledge regarding NNJ, whereas 40.0%, 34.0% and 18.7% had satisfactory, good and poor level of knowledge respectively. The Chi-square test model showed a significant association between previous knowledge of the respondents on NNJ with level of knowledge among the respondents (p= 0.027) and age of the respondents (p=0.012). Conclusion: Awareness should be created among the expecting mothers about neonatal jaundice and encourage them to take preventive measures to avert neonatal mortality and morbidity. Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 121-127